A Probe into the Impact of Teachers Assessment on Students Engagement in EFL Learning : Views From EFL School Teachers - Tarihoran, Widya Amalia; Nasution, Dewi Kesuma (Journal of Education and Teaching Learning, 2024)
Teacher assessment is a crucial factor in fostering students' motivation to improve their foreign language skills and language competency during the learning process. Engaging students in active learning has been proposed as a means to enhance learning outcomes, motivation, and attitudes towards learning. Although previous research acknowledges the significance of assessment in shaping these factors, there is a lack of specific investigation in this area. The objective of this study is to elucidate the intricate correlation between teacher assessment and student engagement in the English as a Foreign Language (EFL) classroom. This research uses a qualitative research design by conducting direct interviews to collect and analyze data. There are 3 of the 4 English teachers at SMP Swasta Al-Muslimin Pandan were included in the study at random as participants. The results of research perceived by EFL school teachers reveal that involving students in the assessment process, such as through self-assessment and peer assessment activities, further enhanced their engagement and ownership of their learning journey.